Characterizing Surface Infiltration Variability in a Small Natural Forest Watershed - Gaur, Murari Lal (Indian Forester, 2003)
The focus of present study is to quantify and delineate the spatial variations infiltration over various soil-vegetation covers existing in a small natural forest watershed located in a part of central India. Several field tests were conducted using double ring infiltrometers. Observed data were utilized for characterizing infiltration and deriving ranges of parameters used in Horton’s Infiltration model. Surface attributes of the watershed were observed and categorized depending upon the prevailing soil-vegetation covers. Infiltration characteristics were determined for these cover complexes which showed vast variations and thus proved dominant influences of the vegetation. The temporal variations were of identical patterns but the magnitudes were differing significantly. Initial infiltration rates were ranging between 26 to 337 mm/hr, while the steady state rates were in the range of 5-24 mm/ha, depending upon the surface attributes oflands at the test locatons. Attempts have been made to develop standard type curves of mass infiltration with their categorical comparison. These results may facilitate researchers for better applications of the modern rainfall-funoff modeling approaches on similar forest watersheds in the region.